1990
DOI: 10.1002/ana.410270509
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of muscle wasting in myotonic dystrophy

Abstract: Myotonic dystrophy is associated with progressive muscular atrophy. In order to determine the mechanism of muscle wasting in this condition, we measured fractional mixed skeletal muscle protein synthesis in the postabsorptive state in 8 patients with myotonic dystrophy, and compared the results with those of 10 normal subjects. Fractional muscle protein synthesis was determined by measuring the increment of 13C leucine in mixed skeletal muscle protein obtained by needle biopsy from the quadriceps muscle during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…It is unlikely that changes in a single splicing event, such as PKM2 expression, would result in the progressive muscle weakness; however, multiple splicing defects in the same signaling or metabolic pathway may accumulate to disrupt muscle function. Given the importance of insulin signaling in protein synthesis and anabolism, the previously reported aberrant splicing of insulin receptors (15) likely results in deficient protein synthesis in skeletal muscle, in agreement with earlier studies suggesting that the muscle weakness in DM1 results from a reduced protein synthesis rate (11). The expression of PKM2 in DM1 muscle can further perturb glucose metabolism and energy homeostasis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is unlikely that changes in a single splicing event, such as PKM2 expression, would result in the progressive muscle weakness; however, multiple splicing defects in the same signaling or metabolic pathway may accumulate to disrupt muscle function. Given the importance of insulin signaling in protein synthesis and anabolism, the previously reported aberrant splicing of insulin receptors (15) likely results in deficient protein synthesis in skeletal muscle, in agreement with earlier studies suggesting that the muscle weakness in DM1 results from a reduced protein synthesis rate (11). The expression of PKM2 in DM1 muscle can further perturb glucose metabolism and energy homeostasis.…”
Section: Discussionsupporting
confidence: 88%
“…Instead, the most prominent histological abnormalities in DM1 are centralized nuclei and slow myofiber (type 1 fiber) atrophy (1). Early studies suggested that reduced protein synthesis and an imbalance of anabolism and catabolism may be responsible for the muscle wasting in DM1 (10,11). Recent studies have shown that abnormal T-tubule biogenesis and calcium signaling, along with increased glycogen synthase kinase 3β (GSK3β) activity, are associated with muscle weakness (12)(13)(14).…”
mentioning
confidence: 99%
“…The myopathy in DM1 has been attributed to factors including altered: (a) protein synthesis [38] (b) contractile protein expression and force generating capacity [39, 40], (c) Ca 2+ -calmodulin-dependent protein kinase activity and phosphorylation of phospholamban [39] and (d) ATP turnover [41]. Additionally, while ASI(-)RyR1 expression is increased in DM1, the mechanism by which lowered resting RyR1 channel activity could contribute to the myopathy was unclear [5].…”
Section: 0 Discussionmentioning
confidence: 99%
“…Some older studies suggest that muscle wasting in patients with DM1 is caused by a defect in the muscle protein synthesis rather than by a defect in accelerated muscle breakdown (11,12). In contrast, another study found that muscle wasting is caused by an elevated protein breakdown in DM1 patients, which could be explained by lower levels of plasma IGF-1 and higher levels of TNF-␣ (20).…”
Section: Discussionmentioning
confidence: 99%